Tinjauan Tentang Penerapan Analisis Swot Dalam Meningkatkan Daya Saing Perusahaan (Studi Kasus Pada King Cafe) - Ayu Afsari; Eva Rachmawati (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
This study aims to determine the marketing strategy at King cafe. This research was tested using SWOT analysis by identifying various internal factors (strengths and weaknesses) and external (opportunities and threats). A good business strategy is needed to deal with increasingly complex and competitive business competition. The method used in this study is a qualitative method. Data collection techniques in research carried out by interview then analyzed by SWOT. The type of data consists of primary and secondary data. The results of the research from the descriptive methodology of SWOT analysis can be obtained by the matrix value of 2.97 internal factors and the value of the matrix of 2.83 external factors. The cafe business that is being run is in cell number five (growth), which is a situation where the organization experiences a period of growth, both in sales, asset profit, or a combination of the three. From the results of the Cartesian diagram, that the King Cafe Business is in quadrant I (one), which is an aggressive strategy